Magical Realism through the Prism of Artistic Conflict - O. I. Osipova (Научный диалог)
The question of the conflict in the works of magic realism is considered. It is reported that works of magical realism spread in the twentieth century in the literature of different countries and took a strong position in Russian literature in recent decades. Attention is paid to iconic works in modern Russian literature, written in the  mainstream of magical realism. The results of the analysis of binary oppositions at the level of the chronotope and the system of characters in the works of M. Petrosyan “House in which ...” and E. Nekrasova “Kalechin-Malechin” are presented. With the help of comparative and intertextual methods, it has been proved that the traditional neorealistic conflict of two worlds, characteristic of the literature of the twentieth century, is depicted in works of magical realism, proceeding not from the principle of opposing two worlds, but on the basis of their interpenetration and the dominance of noumenal reality over the fantastic. It is proved that the commonality of  antinomies and binary oppositions paradigmatically unites these works, this allows us to conclude about the unity of the artistic world of magic realism as a reflection of the author’s position. The typological approach, the search for intertextual connections determine the relevance of the study for modern literary criticism. The novelty of the research lies in the fact that the comparison of texts allows one to see the ways of modeling the conflict in its variants, taking into account the specifics of works of magical realism, in addition, both texts have not yet become an object of analysis through the prism of conflict.